Digital health literacy for COVID-19 vaccination and intention to be immunized: A cross sectional multi-country study among the general adult population - Roy Rillera Marzo; Roy Rillera Marzo; Roy Rillera Marzo; Tin Tin Su; Tin Tin Su; Roshidi Ismail; Mila Nu Nu Htay; Mohammad Yasir Essar; Shekhar Chauhan; Mark E. Patalinghug; Burcu Kucuk Bicer; Titik Respati; et al. (Frontiers Media S.A., 2022)
IntroductionIt is clear that medical science has advanced much in the past few decades with the development of vaccines and this is even true for the novel coronavirus outbreak. By late 2020, COVID-19 vaccines were starting to be approved by national and global regulators, and across 2021, there was a global rollout of several vaccines. Despite rolling out vaccination programs successfully, there has been a cause of concern regarding uptake of vaccine due to vaccine hesitancy. In tackling the vaccine hesitancy and improving the overall vaccination rates, digital health literacy (DHL) could play a major role. Therefore, the aim of this study is to assess the digital health literacy and its relevance to the COVID-19 vaccination.MethodsAn internet-based cross-sectional survey was conducted from April to August 2021 using convenience sampling among people from different countries. Participants were asked about their level of intention to the COVID-19 vaccine. Participants completed the Digital Health Literacy Instrument (DHLI), which was adapted in the context of the COVID Health Literacy Network. Cross-tabulation and logistic regression were used for analysis purpose.ResultsOverall, the mean DHL score was 35.1 (SD = 6.9, Range = 12-48). The mean DHL score for those who answered "Yes" for "support for national vaccination schedule" was 36.1 (SD 6.7) compared to 32.5 (SD 6.8) for those who either answered "No" or "Don't know". Factors including country, place of residence, education, employment, and income were associated with the intention for vaccination. Odds of vaccine intention were higher in urban respondents (OR-1.46; C.I.-1.30-1.64) than in rural respondents. Further, higher competency in assessing the relevance of online information resulted in significantly higher intention for vaccine uptake.ConclusionPriority should be given to improving DHL and vaccination awareness programs targeting rural areas, lower education level, lower income, and unemployed groups.